PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM QUIZ BERBANTUAN APLIKASI BAAMBOOZLE TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN 21 LUBUK LINTAH - Mega Juli Astuti; Ade Irma Suryani; Yoga Suhendra; Siti Aisyah; Sry Apfani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by low student learning outcomes, with only a few students achieving passing grades in Social Studies (IPS). The purpose of this study was to determine the effect of the Team Quiz learning model assisted by the Baamboozle application on Social Studies learning outcomes of fourth-grade students at SDN 21 Lubuk Lintah. The research method used was a quasi-experimental design with a posttest-only group design. The study population was fourth-grade students at SDN 21 Lubuk Lintah, with class IVA as the experimental class using the Team Quiz model assisted by the Baamboozle application and class IVB without using the Team Quiz model. Data collection in this study used a learning outcome test in the form of 21 multiple-choice questions. The data obtained were analyzed using SPSS 27. Based on the analysis results, the average value of the experimental class using the Team Quiz model assisted by the Baamboozle application was 79.89, higher than the average value of the control class without using the Team Quiz model, which was 69.36. With the hypothesis results obtained from the t-test, namely t (count)3,505> t (table)1,673 with a sig.0.001 <0.05. These results indicate that t (count)> t (table) and the sig value <0.05, so that H_0 is rejected and H_1 is accepted. From the results of the study, it is proven that "There is a significant influence of the implementation of the Cooperative Team Quiz learning model assisted by the Baamboozle application on the learning outcomes of social studies in grade IV students of SDN 21 Lubuk Lintah". This study shows that the Team Quiz learning model assisted by the Baamboozle application can be used as an effective learning alternative to improve the social studies learning outcomes of elementary school students.